2021
DOI: 10.1111/1440-1681.13608
|View full text |Cite
|
Sign up to set email alerts
|

The RNA N6‐methyladenosine modulator HNRNPA2B1 is involved in the development of non‐small cell lung cancer

Abstract: The key N 6 methyladenosine (m 6 A) RNA methylation regulator is associated with multiple tumour progression. However, the m 6 A-associated regulators that influence non-small cell lung cancer (NSCLC) development have not been fully clarified. The m 6 A regulator expression pattern of NSCLC patients from The Cancer Genome Atlas (TCGA) dataset was identified. Aberrations of m6A modulators are related to NSCLC development via cBioPortal database. Furthermore, we found that IGF2BP2, IGF2BP3,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Yu et al demonstrated that CACNA1G-AS1 promoted NSCLC cell migratory and invasive abilities through regulating HNRNPA2B1 [ 39 ]. Recently, Jin et al indicated that HNRNPA2B1 promoted NSCLC malignancy through facilitating cell growth and metastasis, suggesting that HNRNPA2B1 is a promising targeted biomarker for therapy of NSCLC [ 40 ]. Herein, LINC01833 could bind to HNRNPA2B1 in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al demonstrated that CACNA1G-AS1 promoted NSCLC cell migratory and invasive abilities through regulating HNRNPA2B1 [ 39 ]. Recently, Jin et al indicated that HNRNPA2B1 promoted NSCLC malignancy through facilitating cell growth and metastasis, suggesting that HNRNPA2B1 is a promising targeted biomarker for therapy of NSCLC [ 40 ]. Herein, LINC01833 could bind to HNRNPA2B1 in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous nuclear ribonucleoprotein A2/B1 (HNRNPA2B1) is a protein that ubiquitously participates in RNA‐binding and pre‐RNA processing, regulating cancer cell metabolism, proliferation, migration, invasion, and apoptosis [ 26–30 ]. HNRNPA2B1 shows high expression in lung cancers [ 31 , 32 ] and serves as a m6A regulator [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture, MTT, colony formation, Transwell assays These assays were conducted as previously reported [6,17,28].…”
Section: Rna Extraction and Real-time Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…YTHDF1 deficiency could affect the translation efficiency of CDK2, CDK4 and cyclin D1 and inhibit NSCLC cell proliferation and lung squamous cell carcinoma progression, while high YTHDF1 expression was associated with better clinical outcome (Shi et al, 2019). Compared with paracancerous tissues, hnRNPA2B1 was highly expressed in NSCLC and could bind to ERK/p53/HDM2 signaling pathway, suggesting that hnRNPA2B1 may be involved in NSCLC pathogenesis (Kim et al, 2021;Jin et al, 2022). In addition, hnRNPC overexpression is associated with later clinical stage and lymph node and distant metastasis, and promotes NSCLC cell proliferation, migration and invasion, possibly through activation of the IFN-a-JAK-STAT1 signaling pathway (Yan et al, 2019).…”
Section: M6a Methylated Reading Protein In Nsclcmentioning
confidence: 99%